Frequency and type of emergency medical teams intervention of in oncological patients from selected areas the Lublin region - Bąk, Jadwiga; Rząca, Marcin; Chrzan-Rodak, Agnieszka; Zarzycka, Danuta (Journal of Education, Health and Sport, 2019)
A steady increase in the incidence of most malignancies has been observed in the structure of Polish society. The National Medical Emergency Service has undergone a number of changes over the last two decades. The fundamental purpose of this system is to provide medical assistance in life-threatening emergencies to every human being. Material and method: The database for the Emergency Medical Team (EMT) interventions from randomly selected areas of the Lublin region was analysed. The data related to all emergency intervention provided by EMTs in the years 2008-2012 and 2004 in the areas of Łęczna, Kraśnik, Lublin, Świdnik. Aim: The aim of the article was to determine the incidence of EMT (Emergency Medical Team) interventions in cancer patients in the population of selected areas of the Lublin region. Keywords: Emergency Medical Team, oncology patient, Lublin region, medical emergency service